Laminate

By using a specific laminated structure of polylactic acid-based resin, water-soluble resin and water-soluble nonwoven fabric in the laminated body, the problem of lack of durability in the dry state in the prior art is solved, and excellent handling and durability are achieved, and suitable for adhesion protection and healing delay.

CN119604412AInactive Publication Date: 2025-03-11TORAY INDUSTRIES INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380055595.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-25
Filing Date
2023-07-25
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the laminate lacks durability in the dry state and is difficult to show excellent effects in adhesion protection and healing delay.

Method used

The laminated structure of an anti-adhesive layer containing a polylactic acid-based resin, a water-soluble film of a water-soluble resin, and a water-soluble nonwoven fabric is adopted, and the handling and durability of the laminated body are improved by specific lamination order and structural parameters, such as the thickness of the anti-adhesive layer, the thickness and adhesion of the water-soluble film and the nonwoven fabric.

Benefits of technology

A laminate with excellent handling and durability in a dry state can effectively prevent adhesion and delay the healing process, thereby improving the stability and service life of medical materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604412A_ABST
    Figure CN119604412A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a laminate which has excellent handling properties when attached to an adherend, has excellent durability in a dry state, and has no difference in characteristics of outermost layers on both surfaces. Provided is a laminate which has excellent handling properties when attached to an adherend by laminating, in the order A / B / C / B / A, an anti-adhesion layer (A) that contains a polylactic acid-based resin and has a thickness of 10-500 nm, a water-soluble film (B) that contains a water-soluble resin and has a thickness of 1-18 [mu] m, and a water-soluble nonwoven fabric (C) that has a thickness of 80-550 [mu] m, in which the density and structural characteristics of the cross section are specified, and which has excellent adhesion properties when attached to the adherend. And has excellent durability in a dry state, and there is no difference between the two surfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminate. Background Art

[0002] One of the complications after surgery in open surgeries, such as abdominal surgery, plastic surgery, and neurosurgery, is adhesion between organs. The problem is that if tissues damaged by drying and oxidation are sutured together during surgery, adhesions may occur during the process of wound healing. In other words, organ tissues that should not be joined are joined together. It is said that adhesions occur with a high probability during surgery, and are sometimes associated with complications that cause serious conditions such as pain, intestinal embolism (intestinal obstruction), and infertility.

[0003] It is difficult to administer medication to treat adhesions that have already formed. In addition, there are cases where intestinal embolism occurs due to adhesions several years after surgery. It is said that the only treatment for adhesions is adhesion removal surgery, which is to perform an incision to remove the adhesion site. In the incision surgery, it is important to prevent adhesions and delay in healing.

[0004] As materials having the above-mentioned anti-adhesion effect and anti-delayed healing effect, it is known in the past that anti-adhesion materials such as gelatin and collagen, which can be expected to be bioabsorbable, are used to physically separate organ tissues. In addition, the anti-adhesion material needs to be retained in the body after surgery and is preferably decomposed after the surgical site is cured. Therefore, it is required to have a low risk of infection, be safe for the organism, and have high decomposition and absorption in the organism.

[0005] It is also known that an anti-adhesion material has multiple functions by laminating multiple layers with specific functions. For example, it is reported that when a laminate of a fiber structure containing a water-soluble polymer and a polylactic acid resin having a thickness of nanometer units is attached to an adherend, the laminate has excellent handling properties due to the thickness of the fiber structure, and by attaching water to the fiber structure after being attached to the adherend, only the layer containing the polylactic acid resin can be left on the tissue, and by providing a layer containing a water-soluble polymer between the polylactic acid resin and the fiber structure, the adhesion between the polylactic acid resin and the fiber structure is improved (Patent Document 1).

[0006] In addition, the laminated body described in Patent Document 1 discloses that: by sandwiching a layer containing a water-soluble polymer between a fiber structure containing a polylactic acid resin having a thickness of nanometer units and a water-soluble polymer, the adhesion and handling properties are improved. However, since the fiber structure containing the water-soluble polymer is exposed to the outermost layer, not only is it possible that the solubility after attachment is deviated due to the uneven weight per unit area of ​​the fiber structure, but it is also easy to dissolve when it is wetted by mistake when attached to the adherend, so there is a possibility that the handling properties during attachment are deteriorated. As a method for improving this problem, a laminated body (Patent Document 2) is disclosed that has both water resistance during handling and water solubility after organ attachment by laminating a film containing a water-soluble polymer on the surface of the fiber structure.

[0007] In addition, the raw materials used in anti-adhesion materials are mostly biocompatible and biodegradable, and are usually protected by air-barrier packaging that is not easily permeable to oxygen or moisture-proof packaging that is not easily permeable to water from the perspective of long-term storage stability. In particular, in order to minimize the impact of material degradation caused by moisture, measures such as sealing dry materials together with the packaging material are sometimes taken to keep the humidity inside the packaging material at a low level for a long time.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 6119863

[0011] Patent Document 2: Japanese Patent No. 7077621 Summary of the invention

[0012] Problems to be solved by the invention

[0013] The laminates described in Patent Documents 1 and 2 disclose the materials, thickness, microstructure (film, fiber), and number of layers to be laminated required to improve handling when attached to an organ, but do not disclose the durability in a dry environment and in a dry state, such as when wrapped in packaging materials or just after being opened from packaging materials.

[0014] Therefore, an object of the present invention is to provide a laminate having excellent handling properties when attached to an adherend and excellent durability in a dry state.

[0015] Means used to solve problems

[0016] The present inventors have conducted intensive studies to overcome the above-mentioned problems and have found the following inventions (1) to (3).

[0017] (1) A laminate comprising: an anti-adhesion layer (A) comprising a polylactic acid resin and having a thickness of 10 to 500 nm, a water-soluble film (B) comprising a water-soluble resin and having a thickness of 1 to 18 μm, and a water-soluble nonwoven fabric (C) comprising a water-soluble resin and having a thickness of 80 to 550 μm, wherein the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C) are laminated in the order of (A) / (B) / (C) / (B) / (A), an image (Y) is subjected to fast Fourier transform, and the obtained power spectrum intensity is converted to decibels. After calculation, the center is set as the origin, the positive x-axis is set as zero degrees, the semi-clockwise direction is set as a positive angle, and the scatter plot obtained by integrating every 5 degrees from 0 degrees to 180 degrees satisfies the following formula 1 when the vertical axis is set as the average intensity (I) and the horizontal axis is set as the angle. The image (Y) is obtained by binarizing the image (X) according to the threshold value at which the separation degree reaches the maximum through the discriminant analysis method, and the image (X) is obtained by cutting with 720×720 pixels from a digital image obtained by observing the cross section at a magnification of 500 times using a scanning electron microscope,

[0018] 0.90≤I 10-45 ÷I max ≤0.99…Formula 1

[0019] (In Formula 1, I 10-45 is the average intensity at angles of 10 to 45 degrees, I max Indicates the maximum average intensity from 0 to 180 degrees.)

[0020] (2) The laminate according to (1), wherein the image (Y) satisfies the following formula 2, the image (Y) being obtained by binarizing the image (X) by a discriminant analysis method according to a threshold value at which the degree of separation is maximized, the image (X) being obtained by cutting out a digital image obtained by observing a cross section at a magnification of 500 times using a scanning electron microscope with 720×720 pixels,

[0021] 0.30≤a÷{a+b}≤0.45…Formula 2

[0022] (In Formula 2, a is the photographic area of ​​the portion of the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C), and b is the photographic area of ​​the void portion surrounded by the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C).)

[0023] (3) The laminate according to (1) or (2), wherein the water-soluble resin is pullulan.

[0024] Effects of the Invention

[0025] The laminate of the present invention has a structural pattern having specific parameters in the cross section of the laminate, thereby being able to suppress embrittlement of the entire laminate in a dry state which is accompanied by changes in the mechanical strength of the water-soluble film and the water-soluble nonwoven fabric. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is an example of a schematic diagram of a cross section of the laminate of the present invention.

[0027] Figure 2 This is an example of an image obtained by photographing the laminate of the present invention using a scanning electron microscope.

[0028] Figure 3 This is an example of an image before Fourier transform is performed on the image of the laminated body of the present invention.

[0029] Figure 4 Yes Figure 3 An example of an image after Fourier transform of an image.

[0030] Figure 5 This is an example of the position and scattergram of the intensity I in the laminate of the present invention.

[0031] Figure 6 It is a schematic diagram showing a method of durability testing of the laminated body of the present invention. DETAILED DESCRIPTION

[0032] Hereinafter, the laminated body of the present invention will be described in detail together with the embodiments.

[0033] It should be noted that, in this specification, "film", "film", "sheet" and "layer" are used with the meaning of a planar structure having two-dimensional expansion. In addition, the "laminated body" of the present invention means a sheet-like structure composed of a plurality of layers obtained by laminating a film and a film comprising a single layer or multiple layers with a nonwoven fabric comprising a single layer or multiple layers. In addition, in this specification, the "cross section of laminated body" refers to: for a sheet-like laminated body, the cut surface generated when cutting in a manner perpendicular to the sheet plane is used with the meaning of the surface observed from a direction perpendicular to the thickness direction.

[0034] The laminate of the present invention has a structure in which the following anti-blocking layer (A), the water-soluble film (B), and the water-soluble nonwoven fabric (C) are laminated in a specific order.

[0035] <Anti-blocking layer (A)>

[0036] Anti-adhesion layer (A) comprises polylactic acid resin, and from the viewpoint of shape following property for adherend, thickness is set to 10nm~500nm, more preferably 10nm~300nm, more preferably 50nm~200nm.If thickness is thinner than 10nm, then sometimes as the water resistance of laminated body is insufficient or difficult to keep the shape as anti-adhesion layer, if thickness exceeds 500nm, then sometimes when being attached to adherend, wrinkle is produced or target attachment position and anti-adhesion layer are easily offset or decomposition in vivo needs time.

[0037] For the purpose of improving mechanical strength, in the anti-adhesion layer (A), relative to the overall 100 mass % of the layer of the polylactic acid resin, an impact resistance modifier of more than 2 mass % and less than 20 mass % may be contained. Preferably, more than 2.5 mass % and less than 15 mass %. The more the content of the impact resistance modifier, the more the effect of improving the impact resistance will be improved, but even if it contains more than 20 mass %, sometimes the significant improvement of mechanical strength cannot be obtained.

[0038] As long as it is the scope that does not damage the effect of the present invention, it is possible to include various additives that are less than 30 mass % relative to the overall 100 mass % of the anti-adhesion layer (A). As these various additives, antioxidants, weathering agents, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet light absorbers, coloring agents, etc. can be used. The lower limit of the content of additives is not particularly limited, and it is also possible to have no problem that 0 mass % is relative to the overall 100 mass % of the anti-adhesion layer (A).

[0039] In addition, as other additives, bioabsorbable materials including gelatin, collagen, hyaluronic acid, chitosan, synthetic polypeptides, etc. can be added to appropriately adjust the biodegradability rate.

[0040] In addition, as long as it is the scope that does not damage the effect of the present invention, it is possible to include inorganic particles or organic particles with a mass % of less than 20% relative to the overall 100% by mass of the anti-adhesion layer (A). As inorganic particles or organic particles, calcium carbonate, titanium oxide, silicon oxide, calcium fluoride, lithium fluoride, aluminum oxide, barium sulfate, zirconium oxide, calcium phosphate, cross-linked polystyrene particles and metal nanoparticles etc. can be listed. The lower limit of the content of inorganic particles or organic particles is not particularly limited, and can be 0% by mass relative to the overall 100% by mass of the anti-adhesion layer (A).

[0041] The anti-adhesion layer (A) of the present invention is transparent, and therefore the attached surface is inconspicuous, so that it can be attached to the skin not only for surgical operations but also as a bandage.

[0042] Furthermore, the anti-adhesion layer (A) can be used as a substrate to support and slowly release various drugs, and can also be used as a drug delivery system.

[0043] <Water-soluble film (B)>

[0044] The water-soluble film (B) in the present invention may be composed of one water-soluble resin or may be composed of two or more water-soluble resins.

[0045] From the viewpoint of the bonding strength to the water-soluble nonwoven fabric (C), the handling property as a laminate, and the shape followability of the adherend, the thickness of the water-soluble film (B) is preferably 1 μm to 18 μm, and more preferably 2 μm to 10 μm. If it is thinner than 1 μm, there is a situation where it is damaged when peeled off from the substrate film, and there is a situation where it is difficult to handle the laminated film state laminated with the anti-adhesion layer due to the lack of stiffness, and it is difficult to carry out the process of attaching to the water-soluble nonwoven fabric (C). If it exceeds 18 μm, there is a situation where wrinkles are generated when attached to the adherend, or it takes time to dissolve in water or an aqueous solution after being attached to the adherend, the adhesion to the adherend is reduced, or creases, cracks, ruptures, and planarity deterioration are likely to occur when the laminate is bent.

[0046] <Water-soluble nonwoven fabric (C)>

[0047] The water-soluble nonwoven fabric (C) in the present invention may be composed of one water-soluble resin or may be composed of two or more water-soluble resins.

[0048] The manufacturing method of the above-mentioned nonwoven fabric is not particularly limited. Dry method, wet method, melt blowing method, spunbond method, etc. can be used to form a fleece-like material, and chemical bonding method, thermal bonding method, needle punching method, water flow interweaving method, etc. can be used to combine fibers to manufacture nonwoven fabrics.

[0049] The thickness of the nonwoven fabric is preferably 80 μm to 2000 μm. When the thickness of the nonwoven fabric is 80 μm or more, the roll transportability of the spinning machine is excellent, and when the thickness is 2000 μm or less, the length of the single winding in the spinning machine is long, and the productivity is excellent.

[0050] It should be noted that the above thickness refers to: according to JIS L1912:1997, 10 pieces of 2500mm in size are taken from the sample 2 The above test pieces were measured using a constant pressure thickness gauge (manufactured by Ozaki Seisakusho Co., Ltd., trade name: PEACOCK (registered trademark), digital gauge model: PDN-21, measuring pressure: 0.5±0.1 kPa, pressure foot area: 2500 mm 2 , micrometer stand model: SIS-6) measure 10 points and get the average value.

[0051] From the viewpoint of solubility in water and fiber strength, the average fiber diameter of the fibers in the nonwoven fabric is preferably 0.001 μm to 100 μm. In addition, the average fiber diameter of the fibers in the nonwoven fabric is more preferably 0.1 μm or more, and more preferably 1 μm or more. If the average fiber diameter of the nonwoven fabric is 0.001 μm or more, the yarn can be stably produced during spinning. In addition, the average fiber diameter of the nonwoven fabric is preferably 100 μm or less, and more preferably 50 μm or less. If the average fiber diameter of the nonwoven fabric is 100 μm or less, sufficient softness can be imparted.

[0052] The weight per unit area of ​​the nonwoven fabric is preferably 1 g / m 2 ~1,000g / m 2 In addition, the weight per unit area of ​​the nonwoven fabric is more preferably 10 g / m 2 More preferably, 15 g / m 2 If the unit area weight of the nonwoven fabric is 1 g / m 2 The above-mentioned nonwoven fabric has a weight per unit area of ​​400 g / m2. 2 Below, more preferably 150g / m 2 If the nonwoven fabric has a unit area weight of 1,000 g / m 2 As a result, the handling of the nonwoven fabric in a roll form becomes easy, and the cushioning properties of the nonwoven fabric can be appropriately suppressed. When laminating with the water-soluble film (B), the pressing pressure on the surface of the fiber structure can be appropriately maintained, allowing for efficient lamination processing.

[0053] The nonwoven fabric may be subjected to a treatment such as pressurization. The pressurization treatment may be performed in any step between the step of obtaining the nonwoven fabric and the step of laminating the nonwoven fabric with the water-soluble film (B). In order to improve the setting property during pressurization, hot pressurization is preferably performed.

[0054] In the present invention, both the water-soluble nonwoven fabric (C) and the water-soluble film (B) contain a water-soluble polymer, so that a laminate having good adhesion between the water-soluble nonwoven fabric (C) and the water-soluble film (B) can be produced. As a laminate, it maintains a stable shape against external forces and has excellent handleability using pliers or hands.

[0055] <Laminate>

[0056] The laminate of the present invention comprises: an anti-adhesion layer (A) comprising a polylactic acid resin and having a thickness of 10 to 500 nm, a water-soluble film (B) comprising a water-soluble resin and having a thickness of 1 to 18 μm, and a water-soluble nonwoven fabric (C) comprising a water-soluble resin and having a thickness of 80 to 550 μm. In addition, the laminate is constructed by laminating in the order of anti-adhesion layer (A) / water-soluble film (B) / water-soluble nonwoven fabric (C) / water-soluble film (B) / anti-adhesion layer (A) from one side. As an example of a schematic diagram of a cross section of the laminate of the present invention, Figure 1 .

[0057] In addition, with respect to the laminate of the present invention, after fast Fourier transform is performed on the image (Y), the obtained power spectrum intensity is converted into decibels, the center is set as the origin, the positive x-axis is set as zero degrees, the semi-clockwise direction is set as a positive angle, and the scatter plot obtained by integrating every 5 degrees from 0 degrees to 180 degrees satisfies the following formula 1 when the vertical axis is set as the average intensity (I) and the horizontal axis is set as the angle. The image (Y) is obtained by binarizing the image (X) according to the threshold value at which the separation degree reaches the maximum by the discriminant analysis method, and the image (X) is obtained by cutting out 720×720 pixels from a digital image obtained by observing a cross section of the laminate using a scanning electron microscope at a magnification of 500 times,

[0058] 0.90≤I 10-45 ÷I max ≤0.99…Formula 1

[0059] (In Formula 1, I 10-45 is the average intensity at angles of 10 to 45 degrees, I max Indicates the maximum average intensity from 0 to 180 degrees.)

[0060] In addition, with respect to the laminate of the present invention, the image (Y) can satisfy the following formula 2, wherein the image (Y) is obtained by binarizing the image (X) by a discriminant analysis method according to a threshold value at which the degree of separation is maximized, and the image (X) is obtained by cutting a digital image obtained by observing a cross section of the laminate at a magnification of 500 times using a scanning electron microscope at 720×720 pixels.

[0061] 0.30≤a÷{a+b}≤0.45…Formula 2

[0062] (In Formula 2, a is the photographic area of ​​the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C), and b is the photographic area of ​​the void portion surrounded by the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C).)

[0063] The cross-sectional thickness of the laminate of the present invention can be measured by the following measurement method. Specifically, for an observation test piece (a cross section of a laminate) produced using a rotary slicer for slice production and surface smoothing (manufactured by Japan Microtome Laboratory), the function of a scanning electron microscope (SEM) such as an ultra-depth multi-angle microscope VHX-D500 (manufactured by KEYENCE) is used to adjust the magnification in the range of 500 times to 100,000 times and observe in such a way that each observation layer falls within 10% to 90% of the viewing angle, thereby obtaining. An example of an image obtained by photographing the laminate of the present invention using a scanning electron microscope is shown in Figure 2 . Here, the thickness of the cross section is defined by the following average value: for a rectangular test piece of 14.7 cm in length and 12.7 cm in width, the observation test piece is taken from 9 points at intervals of 5 cm in a grid shape parallel to the short axis direction or the long axis direction with the center of the test piece as the origin, and the average value is obtained by measurement. When the test piece is less than 14.7 cm in length and 12.7 cm in width and it is impossible to take the observation test piece at intervals of 5 cm, the observation test piece can be taken from multiple test pieces. It should be noted that the cross section can be parallel to the short axis direction or the long axis direction.

[0064] As a pretreatment for the thickness measurement method, in order to prevent charging due to electrons, the surface of the test piece for observation is preferably coated with a conductive material such as gold, platinum, or carbon using an "AUTO FINE COATER JEC-3000FC" (JEOL Ltd.) plasma sputtering device.

[0065] It should be noted that when the thickness of each layer is less than 100 nm and it is difficult to observe using the above method, a transmission electron microscope (TEM) such as "JEM-2100Plus" (manufactured by JEOL Ltd.) can be used, and the magnification is set to 500,000 to 1,000,000 times, and the same observation can be performed. Even if it is difficult to judge, the observed image can be saved, the image can be appropriately enlarged (for example, printed in A3 size, using image enlargement, etc.), and the observed thickness can be calculated.

[0066] In the laminate of the present invention, the method for obtaining the digital image (W) of the laminate cross section is not particularly limited, and the desired image (magnification is 500 times) can be obtained by the same method as the thickness measurement method. In order to facilitate the fast Fourier transform described later, when the image (X) is cut out from the digital image (W) with 720×720 pixels, the field of view of the digital image (W) is photographed with 1600 pixels in the horizontal direction and 1200 pixels in the vertical direction in a manner equivalent to a rectangle with an actual size of 800μm in the horizontal direction and 600μm in the vertical direction, and the thickness of the laminate is confirmed. When the thickness of the laminate is less than 450μm, the image is compressed by 80% in a manner that the entire image is 1280 pixels in the horizontal direction and 960 pixels in the vertical direction. In addition, when the thickness of the laminate is more than 450μm, the image is compressed by 60% in a manner that the entire image is 960 pixels in the horizontal direction and 720 pixels in the vertical direction. 720×720 pixels are cut out from the compressed image.

[0067] The positions are selected so that the center of gravity of the cut laminate image is at the center of the image (X) and the two water-soluble films (B) are most parallel to the upper and lower limits of the region of the image (X).

[0068] In the present invention, the method for binarizing the image (X) is a method for binarizing by using a discriminant analysis method and a threshold value at which the separation degree reaches the maximum (so-called Otsu binarization method). Image information processing can use commercially available image analysis software such as "ScionImage" (manufactured by Scion Corporation). It should be noted that before binarization, the portion other than the laminate (the outside of the laminate) in the image (X) is painted black (masked) so as not to become noise.

[0069] The area calculation of the photographed area (a) of the portion of the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble non-woven fabric (C), and the photographed area (b) of the gap portion surrounded by the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble non-woven fabric (C) can be obtained by counting the number of pixels of the portion, and various image analysis software such as "Analyze Particle" can be used.

[0070] It should be noted that the ratio of the shooting area (a) of the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C) and the shooting area (b) of the gap surrounded by the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C) refers to: for a rectangular test piece of 14.7 cm in the longitudinal direction and 12.7 cm in the transverse direction, the test piece for observation is taken from 9 points with the center of the test piece as the origin and a grid shape parallel to the minor axis direction or the major axis direction at intervals of 5 cm, and the average value obtained by evaluation. It should be noted that when the test piece is less than 14.7 cm in the longitudinal direction and 12.7 cm in the transverse direction and it is impossible to take the test piece for observation at intervals of 5 cm, the test piece for observation can be taken from multiple test pieces. It should be noted that the cross section can be parallel to the minor axis direction or parallel to the major axis direction.

[0071] In addition, for the laminate of the present invention, the image (Y) is analyzed using a fast Fourier transform, wherein the image (Y) is obtained by binarizing the image (X) using a discriminant analysis method according to a threshold value at which the separation degree is maximized, and the image (X) is obtained by cutting a digital image obtained by observing the cross section of the laminate using a scanning electron microscope at a magnification of 500 times and obtaining the image by 720×720 pixels. The fast Fourier transform can be performed using commercially available image analysis software such as "Image-Pro" (manufactured by Media Cybernetics). In addition, decibel conversion can also be performed using programming languages ​​such as "C++", "Java" (registered trademark), "Python" (and multiple program libraries such as OpenCV and NumPy), etc. An example of an image before Fourier transform of the image of the laminate of the present invention is shown in Figure 3 , will be Figure 3 An example of an image after Fourier transformation of an image is shown in Figure 4 .

[0072] It should be noted that for the above-mentioned series of image analyses (trimming, binarization, Fourier transform, area calculation), the machine languages ​​​​"C++", "Mathematica" (registered trademark), "Python" (and multiple program libraries such as "OpenCV", "Numpy", "Matplotlib") can also be used.

[0073] Regarding image processing related to nonwoven fabric alone, some relevant contents are described in “Microstructural Analysis of Fiber Segments In Nonwoven Fabrics Using SEM and Image Processing” (International Nonwovens Journal, Volume 10, No. 2, pp. 26-31, Summer, 2001).

[0074] The laminate of the present invention has a characteristic structure of a specific laminate cross section, so that the strain generated when bending can be dispersed, and excellent durability can be achieved even in a dry state under a low humidity environment. Therefore, even when packaged in a dry state for long-term storage, it is not easily damaged by external forces, and it is not easily broken just after the bag is opened.

[0075] In addition, at the medical site, it can be suitably used for medical products such as wound covering materials and anti-adhesion materials that need to be quickly attached to the adherend, and skin care products, band-aids and other skin external materials. It should be noted that by setting the two sides as anti-adhesion layers containing polylactic acid resins, there is no need to confirm the inside and outside of the face when attached to the adherend, and in addition, there is no difference in durability in the folding direction of the laminate, and it is easy to handle.

[0076] <Base Material>

[0077] The substrate in the section of the method for producing the anti-adhesive layer (A) and the water-soluble film (B) described later will be described.

[0078] The substrate used in the present invention is preferably a film containing a polymer substance. As the material of the film used in the substrate (hereinafter referred to as the substrate film), for example, polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene 2,6-naphthalate; polyamides such as nylon 6 and nylon 12; polyvinyl chloride, ethylene-vinyl acetate copolymer or its saponified product, polystyrene, polycarbonate, polysulfone, polyphenylene ether, polyphenylene sulfide, aromatic polyamide, polyimide, polyamide-imide, cellulose, cellulose acetate, polyvinylidene chloride, polyacrylonitrile, polyvinyl alcohol, and copolymers thereof, etc. can be listed.

[0079] From the viewpoint of ensuring the adhesion between the water-soluble film (B) and the substrate film, and the uniformity of the thickness of the water-soluble film (B) and the anti-adhesion layer (A), the material of the substrate film is preferably a polyester such as polyethylene terephthalate or a polyolefin such as polyethylene and polypropylene. From the aspect of high surface wetting tension, polyesters such as polyethylene terephthalate are particularly preferred.

[0080] Before forming the water-soluble film (B) on the substrate film using the water-soluble resin, the substrate film is preferably subjected to a surface treatment such as a corona discharge treatment, a flame treatment, a plasma treatment, or an ultraviolet irradiation treatment.

[0081] The substrate film may be any of an unstretched film, a uniaxially stretched film, and a biaxially stretched film, but is preferably a biaxially stretched film from the viewpoint of dimensional stability and mechanical properties.

[0082] In addition, the base film may contain various additives.

[0083] The thickness of the substrate film is not particularly limited, but is preferably 2 μm to 1,000 μm, and more preferably 10 μm to 500 μm from the viewpoint of economic efficiency.

[0084] <Polylactic acid resin>

[0085] The polylactic acid-based resin used in the laminate of the present invention refers to a polymer containing poly-D-lactide, poly-L-lactide and poly-D,L-lactide as monomers, and specifically includes polylactic acid, poly-L-lactic acid (L-form), poly-D-lactic acid (D-form) and poly-DL-lactic acid (DL-form).

[0086] In addition, the weight average molecular weight of the polylactic acid resin is preferably 10,000 to 400,000, more preferably 20,000 to 300,000, and further preferably 30,000 to 200,000. It should be noted that the weight average molecular weight of the polylactic acid resin mentioned in the present invention refers to: using gel permeation chromatography (hereinafter referred to as GPC), in a solvent obtained by adding sodium trifluoroacetate to hexafluoroisopropanol (HFIP) in a manner of becoming 5mM and dissolving it, and the weight average molecular weight obtained by calculating according to the polymethyl methacrylate (PMMA) conversion method.

[0087] For the purpose of improving solubility in a solvent when making a coating film coating solution, the above-mentioned polylactic acid resin can be mixed with a homopolymer polylactic acid resin having crystallinity and a homopolymer polylactic acid resin having amorphous properties. In this case, the ratio of the homopolymer polylactic acid resin having amorphous properties can be determined as long as it does not damage the effect of the present invention. In addition, when it is desired to impart higher heat resistance to the layer of the biodegradable material, it is preferred that at least one polylactic acid resin having an optical purity of 95% or more is included in the polylactic acid resin used.

[0088] The polylactic acid resin preferably uses poly-L-lactic acid and / or poly-D-lactic acid as the main component. The main component mentioned here refers to a component in which the component derived from lactic acid is 70 mol% or more and 100 mol% or less in 100 mol% of all monomer components constituting the polylactic acid resin, and preferably uses a homopolymer polylactic acid resin consisting essentially only of poly-L-lactic acid and / or poly-D-lactic acid.

[0089] In addition, the amount of poly D-lactic acid is preferably 4 mol% to 50 mol% relative to the overall 100 mol% of the above-mentioned polylactic acid resin, and more preferably 6 mol% to 13 mol%. If the amount of poly D-lactic acid is 4 mol% or more relative to the overall 100 mol% of the above-mentioned polylactic acid resin, it has moderate solubility in organic solvents, so it is easy to be coated, and if the amount of poly D-lactic acid is 50 mol% or less relative to the overall 100 mol% of the above-mentioned polylactic acid resin, it will not have an adverse effect on metabolism, so it is preferred.

[0090] The polylactic acid-based resin may be a copolymerized polylactic acid-based resin obtained by copolymerizing other monomer components having ester-forming ability in addition to L-lactic acid and D-lactic acid.

[0091] Examples of copolymerizable monomer components include hydroxycarboxylic acids such as glycolic acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 4-hydroxyvaleric acid, and 6-hydroxyhexanoic acid; compounds containing multiple hydroxyl groups in the molecule such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, polyethylene glycol, glycerol, polyglycerol, and pentaerythritol, or derivatives thereof; compounds containing multiple carboxylic acid groups in the molecule such as succinic acid, adipic acid, sebacic acid, fumaric acid, terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 5-sodium sulfoisophthalic acid, and 5-tetrabutylphosphonium sulfoisophthalic acid, or derivatives thereof; and sugars such as glucose, fructose, xylose, galactose, mannose, erythrose, arabinose, sucrose, maltolactose, trehalose, and cellobiose.

[0092] It should be noted that, among the above copolymer components, it is preferred to select a biodegradable component according to the intended use. These copolymer components are preferably contained in an amount of 40 mol% or less based on 100 mol% of all monomer components constituting the polylactic acid-based resin.

[0093] The method for producing the polylactic acid-based resin will be described in detail later, and examples thereof include a method of directly polymerizing lactic acid and a ring-opening polymerization method via lactide.

[0094] About the above-mentioned polylactic acid resin, from the viewpoint of suppressing the strength reduction caused by hydrolysis, giving good durability (long-term storage), the carboxyl terminal concentration in the polylactic acid resin is preferably 30 equivalents / 103kg or less, more preferably 20 equivalents / 103kg or less, and further preferably 10 equivalents / 103kg or less. If the carboxyl terminal concentration in the polylactic acid resin is 30 equivalents / 103kg or less, then the carboxyl terminal concentration that also will become hydrolysis from the catalyst is sufficiently low, therefore, can give good durability in practical use, so preferably. About the lower limit of the carboxyl terminal concentration in the polylactic acid resin, it is not particularly limited, even if infinitely close to 0 equivalent, there is no problem.

[0095] As methods for setting the carboxyl terminal concentration in the polylactic acid resin to 30 equivalents / 103kg or less, there can be listed, for example, a method of controlling it by using a catalyst or thermal history when synthesizing the polylactic acid resin; a method of reducing the thermal history by lowering the processing temperature or shortening the heating time when molding into a layer; and a method of capping the carboxyl terminal of the polylactic acid resin using a reactive compound.

[0096] In the method of using a reactive compound to end-cap the carboxyl terminal in a polylactic acid resin, at least a portion of the carboxyl terminal in the polylactic acid resin is preferably end-capped, and more preferably all of them are end-capped. As the reactive compound, for example, condensation reaction type compounds such as aliphatic alcohols and amide compounds, addition reaction type compounds such as carbodiimide compounds, epoxy compounds, and oxazoline compounds can be listed, and from the viewpoint of not being easy to produce unnecessary by-products during the reaction, it is preferably an addition reaction type compound, wherein, from the viewpoint of reaction efficiency, it is preferably a carbodiimide compound.

[0097] The impact resistance modifier used in the present invention for improving impact resistance is preferably an aliphatic polyester other than a polylactic acid resin, from the viewpoint of having suitable dispersibility in the polylactic acid resin and obtaining a higher effect with a small amount.

[0098] Aliphatic polyesters other than polylactic acid resins are not particularly limited, and specific examples include polyglycolic acid, poly 3-hydroxybutyric acid, poly 4-hydroxybutyric acid, poly 4-hydroxyvaleric acid, poly 3-hydroxycaproic acid; or polycaprolactone, polyethylene adipate, polyethylene succinate, polybutylene succinate, polybutylene succinate / adipate, and the like.

[0099] Furthermore, in order to improve the mechanical strength and maintain biodegradability, it is preferred to use a polybutylene succinate polymer as an aliphatic polyester other than the polylactic acid resin. More preferred are polybutylene succinate and polybutylene succinate / adipate, which have a large effect of improving the mechanical strength and good compatibility with the polylactic acid resin.

[0100] The weight average molecular weight of the polybutylene succinate polymer is preferably 100,000 to 300,000. The polybutylene succinate polymer is obtained by polycondensing 1,4-butanediol and succinic acid.

[0101] The polylactic acid resin can be obtained by, for example, the following method. As raw materials, a lactic acid component of L-lactic acid or D-lactic acid and a hydroxycarboxylic acid other than the aforementioned lactic acid component can be used in combination. In addition, a cyclic ester intermediate of a hydroxycarboxylic acid, such as lactide or glycolide, can also be used as a raw material. Furthermore, dicarboxylic acids, diols, etc. can also be used.

[0102] The polylactic acid resin can be obtained by directly subjecting the raw materials such as lactide and glycolide to dehydration condensation or by ring-opening polymerization of the cyclic ester intermediate. For example, when directly subjecting the raw materials to dehydration condensation, the polymer can be obtained by subjecting lactic acid or lactic acid and hydroxycarboxylic acid to azeotropic dehydration condensation in the presence of an organic solvent, especially a phenyl ether solvent, and preferably by returning the solvent substantially anhydrous by removing water from the solvent distilled by azeotropy to the reaction system, thereby obtaining a high molecular weight polymer.

[0103] It is also known that a high molecular weight polymer can be obtained by ring-opening polymerization of a cyclic ester intermediate such as lactide under reduced pressure using a catalyst such as tin octylate. In this case, a polymer with a small amount of lactide can be obtained by adjusting the conditions for removing water and low molecular weight compounds during heating and reflux in an organic solvent, deactivating the catalyst after the polymerization reaction to suppress the depolymerization reaction, and heat-treating the produced polymer.

[0104] <Water-soluble resin>

[0105] The water-soluble resin used in the present invention is a high molecular weight substance soluble in aqueous solutions such as water, warm water, physiological saline, and glucose solution. Specifically, polyvinyl alcohol or its copolymer, dextran, agarose, pullulan, chitosan, mannan, carrageenan, alginic acid, starch (oxidized starch, etherified starch, dextrin, etc.), amylose, amylopectin, pectin, lentinan, hyaluronic acid, hylan, cellulose derivatives (methylcellulose, ethylcellulose, carboxymethylcellulose, carboxyethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, etc.) and other polysaccharides; gelatin, collagen, elastin, albumin, hemoglobin, transferrin, globulin, fibrin, fibrinogen, keratin sulfate and other polypeptides; copolyesters containing polar groups such as polyvinyl pyrrolidone and sulfoisophthalic acid; vinyl polymers such as polyhydroxyethyl methacrylate or its copolymer; acrylic polymers, carbamate polymers, ether polymers, etc.

[0106] In addition, polymers obtained by modifying these various polymers with functional groups such as carboxyl groups, amino groups, and hydroxymethyl groups can also be preferably used. Among them, polyvinyl alcohol and pullulan are preferred from the viewpoints of production cost, availability, and sanitation.

[0107] The polyvinyl alcohol is a saponified product of polyvinyl acetate, and the saponification degree is preferably 80 mol% to 99.9 mol%, more preferably 85 mol% to 98 mol%. If the saponification degree of the polyvinyl alcohol is 99.9 mol% or less, the solubility of the obtained water-soluble nonwoven fabric and water-soluble film (B) in water or aqueous solution is within a preferred range.

[0108] It should be noted that the polyvinyl alcohol in the present invention also includes a polyvinyl alcohol copolymer. As the polyvinyl alcohol copolymer, the vinyl alcohol unit is preferably 80 mol% to 98 mol%, more preferably 85 mol% to 98 mol%.

[0109] The saponification degree is the ratio (mol%) of the molar number of the vinyl alcohol unit to the total molar number of the structural unit (typically, vinyl ester unit) and the vinyl alcohol unit of the polyvinyl alcohol or its copolymer that can be converted into the vinyl alcohol unit by saponification. It should be noted that the saponification degree can be measured according to JIS K6726:1994.

[0110] Pullulan is usually advantageous from the viewpoint of obtaining ease and price, therefore, it is advantageous to use the pullulan produced by culturing yeast of the genus Pullulan etc. in a culture medium containing starch decomposition products. For example, pullulan (Lin Yuan system of Co., Ltd., Japanese Pharmacopoeia pullulan) can be suitably used. Wherein, it is not limited to them, and other pullulan products can also be used within the scope of not exceeding the purpose of the present invention. In addition, it is also possible to use the maltotriose of derivatization as a repeating unit by modification such as esterification of any substitution degree as required.

[0111] The weight average molecular weight of the pullulan used in the present invention is usually preferably 10,000 to 1,000,000, preferably 50,000 to 500,000. It should be noted that by selecting the weight average molecular weight and molecular weight distribution of the pullulan, the desired dissolution rate can be adjusted. It also varies depending on the other ingredients mixed. If the weight average molecular weight is more than 10,000, it is easy to form a film, so it is preferred, if it is less than 1,000,000, it is preferred for dissolution in an aqueous solvent.

[0112] In the present invention, more than two kinds of water-soluble resins can be mixed.Thus, it is possible to obtain a film that is also good with the adhesion of polylactic acid resin in addition to the high mechanical strength of the film and the resolubility of being dissolved in the aqueous solution, so it is preferred.It should be noted that the weight-average molecular weight of the water-soluble resin mentioned in the present invention refers to: using GPC, in a solvent obtained by adding sodium chloride to distilled water in a manner of becoming 0.1M and dissolving it, and the weight-average molecular weight obtained by calculating using the conversion method of pullulan, maltopentaose, and glucose benchmarks.

[0113] As long as the effect of the present invention is not impaired, the amount of various additives added may be 30% by mass or less relative to 100% by mass of the total water-soluble resin. The lower limit is not particularly limited, and there is no problem that the amount of various additives added is 0% by mass relative to 100% by mass.

[0114] As these various additives, antioxidants, heat stabilizers, lubricants, crystal nucleating agents, ultraviolet light absorbers, X-ray absorbers, coloring agents, etc. can be used. In addition, if it is a scope that does not damage the effect of the present invention, then inorganic particles or organic particles can contain less than 20 mass % relative to the overall 100 mass %. The lower limit is not particularly limited, and the addition of these various additives is 0 mass % relative to the overall 100 mass % and there is no problem. For example, calcium carbonate, magnesium oxide, titanium oxide, silicon oxide, calcium fluoride, lithium fluoride, aluminum oxide, barium sulfate, zirconium oxide, calcium phosphate, cross-linked polystyrene particles, metal nanoparticles such as gold and silver, etc. can be used.

[0115] <Coating containing aliphatic polyester>

[0116] As a coating agent containing polylactic acid resin, a solution in which the constituent components are uniformly dissolved is preferred. As a solvent, there is no particular limitation, and it is preferred to use at least one solvent selected from butanol, chloroform, cyclohexane, acetonitrile, dichloromethane, dichloroethane, ethyl acetate, ethyl propionate, ethyl ether, dipropyl ether and toluene, or a mixed solution of two or more thereof. From the viewpoint of productivity and handling, dichloromethane and ethyl acetate are particularly preferred.

[0117] The solid content concentration of the coating agent containing the polylactic acid resin is not particularly limited, but is preferably 1.0% by mass or more and preferably 10% by mass or less from the viewpoint of productivity such as coating viscosity, drying efficiency, and coating properties.

[0118] In order to impart coating properties, other organic compounds may be contained in the solution as a third component within a range in which the stability of the coating agent containing the polylactic acid-based resin is maintained.

[0119] <Coating agent containing water-soluble resin>

[0120] The coating agent containing the water-soluble resin can be used for preparing the water-soluble nonwoven fabric (C), the water-soluble film (B), and the aqueous solution when laminating the water-soluble nonwoven fabric (C) and the water-soluble film (B).

[0121] As the coating agent containing the water-soluble resin, a solution in which the constituent components are uniformly dissolved is preferred. As the solvent, water or a mixed solution of water and a lower alcohol is preferably used. A mixed solution of water and a lower alcohol is more preferably used.

[0122] When used to produce a water-soluble film (B), the solid content concentration of the coating agent containing the water-soluble resin is preferably 1.0% by mass or more and preferably 15% by mass or less from the viewpoint of productivity such as liquid feeding property, drying efficiency, and coating property. If a high-concentration coating agent of more than 15% by mass is used, the solution viscosity may become too high, making it difficult to control the thickness of the water-soluble film (B), and if a low-concentration coating agent of less than 1.0% by mass is used, coating may fall off due to craters or the like.

[0123] In addition, in order to impart coating properties, other water-soluble organic compounds may be included as a third component in the mixed solvent as long as the coating containing the water-soluble resin maintains stability. Examples of the water-soluble organic compound include alcohols such as methanol, ethanol, n-propanol, and isopropanol; glycols such as ethylene glycol and propylene glycol; glycol derivatives such as methyl cellosolve, ethyl cellosolve, and n-butyl cellosolve; polyols such as glycerol and waxes; ethers such as dioxane; esters such as ethyl acetate; and ketones such as methyl ethyl ketone. In addition, from the viewpoint of solution stability, the pH of the dispersion solution is preferably 2 to 11.

[0124] When used for a water-soluble nonwoven fabric (C), from the viewpoint of productivity such as wire drawing properties and drying efficiency, it is preferably 10% by mass or more, and preferably 30% by mass or less. If a high concentration solution exceeding 30% by mass is used, the solution viscosity sometimes becomes too high and it is difficult to eject from a spinneret. When it is less than 10% by mass, the shot generation rate sometimes becomes high, which impairs the appearance.

[0125] In the case of an aqueous solution for laminating a water-soluble nonwoven fabric (C) and a water-soluble film (B), it is preferably 20% by mass or less from the viewpoint of productivity such as ejection, drying efficiency, and lamination. If a high concentration solution exceeding 20% ​​by mass is used, the viscosity of the solution sometimes becomes too high, resulting in clogging of the spray nozzle.

[0126] <Manufacturing method>

[0127] Next, a typical method for producing the laminate of the present invention will be described.

[0128] [Preparation method of coating]

[0129] The preparation method of the coating agent containing water-soluble resin and the coating agent containing polylactic acid resin is not particularly limited. When various additives such as crosslinking agents and particles are added within the range that does not impair the effect of the present invention, it is preferred that the polymer and the additives are uniformly dispersed in the coating agent. As required, the following methods can be used: using a heater or the like to increase the solvent temperature and increase the solubility of the polymer; or using a homogenizer, jet mixer, ball mill, bead mill, kneader, sand mill, three-roll mill, etc. that applies shear force or shear stress to perform mechanical forced dispersion treatment.

[0130] [Method for producing laminated body]

[0131] The method for producing the laminate in the present invention is not particularly limited, and for example, the following method can be used.

[0132] (1) A water-soluble film (B) containing a water-soluble resin is prepared on a base film, and an anti-blocking layer (A) containing a polylactic acid-based resin is formed thereon.

[0133] (2) The formed laminated film in which the water-soluble film (B) and the anti-blocking layer (A) are laminated is mechanically peeled off from the base film to separate the base film and the laminated film.

[0134] (3) The nonwoven fabric (C) containing the water-soluble resin is laminated in a manner that the water-soluble film surface (B) of the above-mentioned laminated film contacts the water-soluble nonwoven fabric (C). Thereafter, on the other side of the water-soluble nonwoven fabric (C), the water-soluble film (B) surface of the laminated film prepared separately in (2) is laminated in a manner that the water-soluble nonwoven fabric (C) contacts. As a bonding method, a method in which the surface of the water-soluble film (B) or the water-soluble nonwoven fabric (C) is softened or dissolved by heat, an aqueous solution, etc., so as to bond or weld the surface of the water-soluble film (B) or the water-soluble nonwoven fabric (C) can be used.

[0135] [Method for producing water-soluble nonwoven fabric (C)]

[0136] The production method is not particularly limited, but dry spinning, in which a spinning stock solution obtained by dissolving the spinning stock solution in a solvent is extruded through a nozzle into heated air and the solvent is evaporated and removed, is suitable because it can be widely applied to various types of water-soluble resins.

[0137] [Method for producing anti-adhesion layer (A) and water-soluble film (B)]

[0138] 1. Film forming method

[0139] The coating method is not particularly limited, and examples thereof include gravure coating, direct lip coating, slit coating, comma coating, inkjet, screen printing, etc. The substrate is not particularly limited, and examples thereof include glass plates, metal plates, plastic films, etc. From the viewpoint of economic efficiency, it is desirable to use a plastic film as the substrate film, and a plastic film having a smooth surface is particularly desirable.

[0140] When a biaxially stretched film of polyester such as polyethylene terephthalate or polyolefin such as polypropylene is used as the substrate film, either off-line coating after the biaxially stretched film forming step or in-line coating during the biaxially stretched film forming step can be used.

[0141] When using online coating, it is preferably applied before the film is heat-fixed. Heat fixing refers to: by keeping the stretched film at a temperature higher than the stretching temperature and lower than the melting point of the film for heat treatment, the film is crystallized. Therefore, it is preferred to apply to an unstretched film, a film just after uniaxial stretching along the length direction or the width direction, or a film just after biaxial stretching. More preferably, the film just after uniaxial stretching is applied, and it is further preferred that the film is further stretched and heat-fixed along one axis or more. The drying method of the coating can use a hot roller contact method, a thermal medium (air, oil, etc.) contact method, an infrared heating method, and a microwave heating method, etc.

[0142] About the method of forming a coating on a substrate film by off-line coating, from the viewpoint of being able to carry out film coating at high speed, it is suitable to disperse the constituent components of the coating film in various solvents and carry out gravure coating, reverse coating, spraying, kiss coating, comma coating, die coating, knife coating, air knife coating or metering rod coating. The substrate film is more preferably subjected to adhesion promotion treatment before coating, such as corona discharge treatment in air, nitrogen, nitrogen / carbon dioxide mixed gas, other atmospheres, plasma treatment under reduced pressure, flame treatment or ultraviolet treatment, etc. Further, anchoring treatment can be implemented using anchoring treatment agents such as urethane polymers, epoxy polymers or polyethylene imine.

[0143] Drying of the coating film for obtaining the water-soluble film (B) containing the water-soluble resin is preferably carried out at a temperature in the range of 60° C. to 180° C. in the case of off-line coating, and in the range of 80° C. to 250° C. in the case of in-line coating. The drying time is preferably 1 to 60 seconds, more preferably 3 to 30 seconds.

[0144] The drying of the coating film for obtaining the anti-blocking layer (A) containing a polylactic acid-based resin is preferably carried out at a temperature in the range of 60° C. to 110° C. in the case of off-line coating, and in the range of 80° C. to 180° C. in the case of in-line coating. The drying time is preferably 1 to 60 seconds, more preferably 3 to 30 seconds.

[0145] It should be noted that it is desired to laminate on the substrate film in the order of substrate film / water-soluble film (B) / anti-adhesion layer (A), and as long as the peelability of the laminated film from the substrate film is not impaired, it can be substrate film / anti-adhesion layer (A) / water-soluble film (B).

[0146] 2. Peeling off from the base film

[0147] Next, the laminated film in which the water-soluble film (B) and the anti-blocking layer (A) were laminated was mechanically peeled off from the base film.

[0148] 3. Fixing of laminated film on support

[0149] Then, in order to easily realize the handling property when laminating operation is performed with water-soluble nonwoven fabric (C), laminated film is arranged on support in the order of support / anti-adhesion layer (A) / water-soluble film (B). Support is not particularly limited, and glass plate, metal plate, plastic film etc. can be listed. From the viewpoint of economy, plastic film is preferably used as support, particularly preferably plastic film with surface release.

[0150] 4. Fabrication of laminated body

[0151] There is no particular limitation on the method for laminating the laminated film and the water-soluble nonwoven fabric (C). The method includes softening the water-soluble film (B) surface of the laminated film or one surface of the water-soluble nonwoven fabric (C) by heat and crimping the two together. The surface of the water-soluble film (B) surface or one surface of the water-soluble nonwoven fabric (C) is dissolved by a water-soluble resin, and the two are crimped and fused together. The same operation is performed on the other surface of the water-soluble nonwoven fabric (C), thereby forming a laminated body stacked in the order of anti-adhesion layer (A) / water-soluble film (B) / water-soluble nonwoven fabric (C) / water-soluble film (B) / anti-adhesion layer (A).

[0152] The aqueous solution is not particularly limited, and examples thereof include pure water, alcohol aqueous solution, mineral dispersion solution, drug dispersion aqueous solution, water-soluble resin solution (20% by mass or less), etc. From an economical point of view, pure water is preferred.

[0153] As described above, since the water-soluble resin is softened, dissolved and bonded using heat or water, the thickness of each layer of the nonwoven fabric and the water-soluble film (B) may be smaller after lamination than before lamination.

[0154] [Method of spraying water or aqueous solution]

[0155] The spraying method of the water or aqueous solution is not particularly limited, as long as the liquid can be widely and evenly dispersed in a fine shape using a sprayer such as a sprayer or a shower, for example, a pressure storage sprayer, a nozzle spray method (two-fluid nozzle, three-fluid nozzle, four-fluid nozzle), an inkjet method, etc. can be used. In addition, there are air spraying, airless spraying, and electrostatic methods. The air spraying method varies according to the spraying principle, and the liquid is sprayed from the spray gun together with compressed air in a mist state. The airless spraying method is a liquefied atomization method that does not use air but applies pressure to the liquid itself to spray fine water particles from a nozzle with a small aperture.

[0156] The temperature of the sprayed water or aqueous solution is not particularly limited, but is preferably 5°C to 35°C from the viewpoint of shape stability of fine water particles. Regarding the environment during the spraying operation, from the viewpoint of operability, the temperature is preferably 5°C to 35°C, and the humidity is preferably 45%RH to 85%RH. Furthermore, from the viewpoint of shape stability of fine water particles, the temperature is preferably 10°C to 25°C, and the humidity is preferably 45%RH to 65%RH. The average water particle size is preferably 1 to 100 μm. The average water particle size mentioned here means: at a location corresponding to the location just before the water particles ejected vertically from the spray nozzle hit the nonwoven fabric, the particle size of 10,000 water particles is measured using a phase Doppler flow meter, which is taken as one measurement, and the Sauter average particle size is measured 3 times at each point of a grid with a spacing of 10 mm relative to the surface bonded with the nozzle vertically as the center, and the total average value thereof is obtained.

[0157] The water adhesion density of the sprayed water or aqueous solution to the nonwoven fabric is preferably 1.9 g / m from the viewpoint of the durability of the laminate in a dry state. 2 From the viewpoint of adhesion between the laminated film and the nonwoven fabric, the preferred thickness is 0.7 g / m 2 From the viewpoint of production efficiency, it is preferably 1.6 g / m 2 Below and 1.0g / m 2 The water adhesion density mentioned here is calculated as follows: at a location equivalent to the location just before the water particles ejected vertically from the spray nozzle hit the nonwoven fabric, 4 water-sensitive paper sheets (5 cm square) are placed horizontally relative to the surface that is attached with the nozzle vertically as the center. After the spraying of water or aqueous solution is completed, the weight of the wetted water-sensitive paper sheets is measured within 10 seconds using an electronic balance, and the weight difference between the weight of each water-sensitive paper sheet before the spraying is calculated, and the value is divided by the area of ​​the water-sensitive paper (5 cm square) for calculation. In the case where the spray pattern (wetting trace) is anisotropic, the distance between the spray nozzle and the water-sensitive paper can be kept constant and the sprayer can be appropriately shaken in the horizontal direction.

[0158] The spraying time of water or an aqueous solution is preferably 20 seconds or less from the viewpoint of solubility of nonwoven fabric fibers, and more preferably 10 seconds or less from the viewpoint of production efficiency.

[0159] From the viewpoint of natural drying of the water-soluble resin, the time from the completion of spraying of water or an aqueous solution to the lamination of the laminated film and the nonwoven fabric is preferably within 30 seconds, and more preferably close to 0 seconds from the viewpoint of production efficiency.

[0160] [Attachment method]

[0161] There is no particular limitation on the method for laminating the water-soluble nonwoven fabric (C) to the water-soluble film (B) surface of the laminated film of the anti-adhesion layer (A) and the water-soluble film (B), and there are methods including: a method of sandwiching and pressing between flat plates such as metal when cut into individual pieces; a method of sandwiching and pressing between two rollers when they are continuous long strips, etc.

[0162] Example

[0163] Hereinafter, examples and comparative examples (Examples 1 to 14 and Comparative Examples 1 to 9) of the laminate according to the present invention will be described. First, the characteristic evaluation method used in the present invention is as follows.

[0164] (1) Measurement of thickness of each component of the laminate (anti-adhesion layer (A), water-soluble film (B), water-soluble nonwoven fabric (C))

[0165] A rectangular test piece of 14.7 cm in length and 12.7 cm in width was placed on a table without overlapping and left to stand for more than 48 hours under standard conditions. Afterwards, an observation test piece made by a rotary slicer for sheet making and surface flattening (made by Japan Microtome Research Institute) was coated with gold using "AUTO FINE COATER JEC-3000FC" (Japan Electronics Co., Ltd.) under the conditions of sputtering time: 120 seconds and current value: 30 mA. It should be noted that the standard state refers to: according to JIS L01055.2 (2006), the temperature is 20±2°C and the relative humidity is 65±4%.

[0166] Using an ultra-depth multi-angle microscope "VHX-D500" (manufactured by KEYENCE Co., Ltd.) and a transmission electron microscope "JEM-2100Plus" (manufactured by JEOL Ltd.), a rectangular test piece measuring 14.7 cm in length and 12.7 cm in width was measured for a cross section at 9 points with the center as the origin and in a grid pattern parallel to the short axis direction or the long axis direction at intervals of 5 cm, and the average value obtained was calculated.

[0167] (2) Ratio of the shooting area (a) to the shooting area (b)

[0168] In the same manner as in (1), the cross section of the laminate was observed at a magnification of 500 times using an ultra-depth multi-angle microscope "VHX-D500" (manufactured by KEYENCE Corporation) for the observation test piece to obtain a digital image (W).

[0169] Furthermore, a trimming program created using the programming language "Python" was used to cut out a digital image (X) with 720×720 pixels from the above image (W). It should be noted that when cutting out the image (X) from the digital image (W), the center of gravity of the cut laminate image became the center of the image (X), and the positions of the two water-soluble films (B) were adjusted in a manner that they were most parallel to the upper and lower limit lines of the digital image (X) area as a whole.

[0170] Furthermore, after the outside of the laminated body was painted black (masked), the image was binarized using a processing program of the Otsu binarization method created using the programming language "Python".

[0171] Furthermore, by using the area calculation program made by the programming language "Python", the shooting area (a) of the water-soluble nonwoven fabric (C), the water-soluble film (B) and the anti-adhesion layer (A), and the shooting area of ​​the gap surrounded by the water-soluble nonwoven fabric (C), the water-soluble film (B) and the anti-adhesion layer (A), the number of pixels of each corresponding part is counted and calculated. Specifically, in the image obtained by binarizing the digital image (X), the portion of the white (pixel value of 255 in 256-level grayscale) pixels is set as the shooting area of ​​the portion of the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C), and the portion of the black (pixel value of 0 in 256-level grayscale) pixels is set as the shooting area of ​​the gap surrounded by the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C). In addition, the area {a+b} of the entire laminate including the void portion is calculated by subtracting the area of ​​the masked portion calculated separately from the total number of pixels of the image (Y).

[0172] The following ratio (r1) is calculated by the following formula 3 using the numerical values ​​obtained above.

[0173] r1=a÷{a+b}…Formula 3

[0174] It should be noted that the value of r1 is rounded to the third decimal place.

[0175] The ratio (r1) refers to the apparent density of the laminate obtained by a digital image of the laminate cross section. If r1 is 0.30 or more, the laminate has sufficient stiffness and excellent handleability. If r1 is 0.45 or less, the laminate can absorb the mechanical load generated during bending without damage.

[0176] (3) Spectral peak position and intensity ratio (r2)

[0177] First, using the image (Y) obtained in (2) above, the direction in which the water-soluble film (B) faces is set as the x-axis, and the direction perpendicular to the x-axis is set as the y-axis. A calculation program created using the programming language "Python" is used to perform a fast Fourier transform on the image (Y), and then the power spectrum intensity is converted into decibels to obtain a spectral image.

[0178] Furthermore, the center of the spectrum image obtained above is set as the origin, the positive x-axis is set as zero degrees, the semi-clockwise direction is set as the positive angle, and the intensity is integrated and averaged at every 5 degrees from 0 degrees to 180 degrees. Using the average intensity (I) thus obtained, a scatter plot is prepared with the horizontal axis as the angle and the vertical axis as the average intensity (I). The position of the peak of the following average intensity (I) is read. Furthermore, the average intensity (I) at an angle of 10 to 45 degrees is calculated using the following formula 4. 10-45 ) relative to the maximum average intensity (I max ) ratio (r2).

[0179] r2=I 10-45 ÷I max ...Formula 4

[0180] It should be noted that the value of r2 is rounded to the third decimal place. An example of a scatter plot obtained based on the positions of the series of intensities I is shown in Figure 5 .

[0181] The ratio (r2) represents the degree to which the component of 10 to 45 degrees contributes to the structure pattern of the laminate, based on the angle component showing the strongest feature, in the spectrum obtained by Fourier transform of the structure pattern made by the resin constituting the laminate, obtained by the digital image of the laminate cross section. r2 is preferably greater than 0.90, and is expected to be infinitely close to 1.0. If r2 is greater than 0.90, the laminate can absorb the mechanical load generated during bending and is less likely to break.

[0182] (4) Durability test

[0183] Figure 6A schematic diagram showing the durability test method of a laminate is shown in . In a drying room at a temperature of 20°C and a humidity of less than 1% RH, a rectangular test piece of 14.7 cm in length and 12.7 cm in width is placed on a platform without overlapping and left to stand for more than 48 hours. Thereafter, in the drying room, the test piece is manually bent 180 degrees in the horizontal direction so that the area (and the horizontal length) of the test piece becomes half, and then temporarily restored to the original plane (first bend). For the same test piece, the test piece is further manually bent 180 degrees in the longitudinal direction along the same side as the first bend so that the area (and the horizontal length) of the test piece becomes half, and then restored to the original plane (second bend). Next, for the same test piece, for the reverse side of the first bent surface, it is similarly bent 180 degrees in the horizontal direction and restored to the original plane (third bend), and is bent 180 degrees in the longitudinal direction and then restored to the original plane (fourth bend).

[0184] The second and fourth bends were visually checked for cracking. No cracking after four bends was rated S, no cracking after the second bend but cracking after the fourth bend was rated A, and cracking after the second bend was rated B.

[0185] (5) Water resistance test

[0186] In a laboratory in a standard state, a rectangular test piece of 14.7 cm in length and 12.7 cm in width is placed on the platform without overlapping, and is left to stand for more than 48 hours. Thereafter, the center of the test piece is set as the origin and 9 points in a grid parallel to the minor axis direction and the major axis direction are presented at intervals of 5 cm, and a position of 10 mm is added from the upper surface of the test piece to the front end of the micropipette. The water droplet is set as the start time when it contacts the test piece, and the shape change of the test piece after 15 seconds is visually observed. For the transparency associated with the dissolution of the laminate, the situation that does not occur after 15 seconds is set as evaluation S, the situation that occurs within 15 seconds but does not occur after 5 seconds is set as evaluation A, and the situation that dissolves in less than 5 seconds is set as evaluation B.

[0187] (6) Fit test

[0188] A rectangular test piece with a length of 14.7 cm and a width of 12.7 cm was cut into a square (3 cm × 3 cm), and placed in a watch glass filled with pure water to dissolve the water-soluble resin to make a single film with only the anti-adhesion layer (A). Spray 100 mg of pure water, and attach the pre-taken anti-adhesion layer (A) to the center of a wet square polyester film (Toray Industries, Inc., "Lumirror" (registered trademark) #100T60, size: 5 cm × 5 cm), and press it with silicone rubber (Kyowa Kogyo Co., Ltd., hardness: 20 degrees, size: 3 cm × 1 cm) that has been dried for 5 seconds to make it close. Next, the polyester film with the anti-adhesion layer (A) attached was placed vertically in a constant temperature and humidity chamber (ESPEC Co., Ltd., LHU-113) at a temperature of 25°C and a relative humidity of 90%, and left in this state for more than 1 hour to remove excess water from the test piece.

[0189] Next, the polyester film with the anti-adhesion layer (A) attached was taken out from the constant temperature and humidity machine, and the polyester film and the anti-adhesion layer (A) were rubbed 10 times with a finger at a weight of 800 to 900 g from the anti-adhesion layer (A) side to determine whether the polyester film and the anti-adhesion layer (A) were offset. The ends of the anti-adhesion layer (A) or the interference fringes caused by the film were visually confirmed, and no offset was set as evaluation A, and offset or the test piece could not be confirmed as evaluation B.

[0190] Hereinafter, the material devices used in Examples 1 to 14 and Comparative Examples 1 to 9 will be described respectively.

[0191] [Base film used]

[0192] (Polyester film-1 (hereinafter referred to as "PET-1"):

[0193] Biaxially stretched polyester film (manufactured by Toray Industries, Inc., “Lumirror” (registered trademark), type: T60, thickness: 100 μm).

[0194] [Polylactic acid resin used]

[0195] (Polylactic acid resin-1 (hereinafter referred to as "PLA-1")):

[0196] The poly-L-lactic acid-D-lactic acid copolymer (PURASORB (registered trademark) PDL20 manufactured by Corbion) was 50 mol% of poly-D-lactic acid based on the total amount and had a weight average molecular weight of 400,000 in terms of PMMA.

[0197] (Polylactic acid resin-2 (hereinafter referred to as "PLA-2")):

[0198] The amount of poly D-lactic acid was 12 mol% based on the total amount and the weight average molecular weight in terms of PMMA was 200,000 (4060D manufactured by Nature Works).

[0199] (Polylactic acid resin-3 (hereinafter referred to as "PLA-3")):

[0200] The following three raw materials were mixed in a flask while being heated at 110°C under an argon gas stream.

[0201] ·L-Lactide

[0202] (Purasorb (registered trademark) L manufactured by Corbion): 220 g

[0203] Glycolide

[0204] (Purasorb (registered trademark) G manufactured by Corbion): 40 g

[0205] Pentaerythritol polyethylene glycol

[0206] (SUNBRIGHT (registered trademark) PTE-10000S manufactured by NOF Corporation, molecular weight 10,000): 60 g

[0207] Next, the mixture was heated to 100°C, and 0.32 g of tin II ethylhexanoate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to react to obtain a block copolymer. The obtained polymer was dissolved in chloroform, washed with dilute hydrochloric acid, and then added dropwise to a significantly excessive amount of acetone. A polylactic acid-polyglycolic acid-polyethylene glycol block copolymer (PLA-3) was obtained as a precipitate.

[0208] In addition, use 1 The integral value of the signal derived from the chemical shift of the protons of the characteristic chemical structures of each of the polyhydroxyalkanoic acid and the polyalkylene glycol, the number of hydrogen atoms contained in the repeating unit, and the molecular weight of the repeating monomer, obtained by evaluating H-NMR (device name: EX-270, measurement frequency: 400 MHz, measurement solvent: deuterated chloroform, accumulation number: 8 times, measurement temperature: room temperature (about 25° C.)), the ratio of the number of moles of lactic acid to the number of moles of glycolic acid (1.0) was 1:4. In addition, the mass ratio of the polyethylene glycol block to the total mass was 6%.

[0209] The PMMA-equivalent weight average molecular weight of PLA-3 determined by GPC was 160,000. In the preparation of the coating solution used for forming the anti-blocking layer (A), dichloromethane was used as a solvent.

[0210] (Polylactic acid resin-4 (hereinafter referred to as "PLA-4")):

[0211] A polylactic acid-polyethylene glycol block copolymer (PLA-4) was obtained in the same manner as in the preparation method of PLA-3 except that the raw materials were changed as follows.

[0212] DL-Lactide:

[0213] (Purasorb (registered trademark) DL manufactured by Corbion): 340 g

[0214] ·Eight-branched polyethylene glycol derivatives

[0215] (SUNBRIGHT (registered trademark) HGEO-150CS manufactured by NOF Corporation, molecular weight 15,000): 60 g

[0216] It should be noted that the weight average molecular weight of PLA-4 based on PMMA conversion by GPC is 110,000. The mass ratio of the polyethylene glycol block to the total mass is 13%, and the value obtained by dividing the average molecular weight of the polylactic acid block by the number of branches 8 is 12,000. In addition, when preparing the coating solution used for film-forming the anti-adhesion layer (A), dichloromethane is used as a solvent.

[0217] [Water-soluble resin used]

[0218] (Pullulan-1)

[0219] The weight average molecular weight is about 300,000, and the kinematic viscosity is 100-180 mm 2 / sec (viscosity measurement conditions: temperature 30°C, solid content concentration 10% by mass aqueous solution) of pullulan (Japanese Pharmacopoeia Pullulan).

[0220] (Polyvinyl alcohol-1 (hereinafter referred to as "PVA-1"))

[0221] Polyvinyl alcohol (JP-10 manufactured by JAPAN VAM & POVAL CO., LTD.) having a saponification degree of 88 mol% and a viscosity of 10 mPa·s (4 mass % aqueous solution, 20° C.).

[0222] (Polyvinyl alcohol-2 (hereinafter referred to as "PVA-2")

[0223] Polyvinyl alcohol (manufactured by JAPAN VAM & POVAL CO., LTD., JM-17) having a saponification degree of 96.5 mol% and a viscosity of 27.5 mPa·s (4 mass % aqueous solution, 20° C.).

[0224] (Gelatin-1)

[0225] Japanese Pharmacopoeia purified gelatin (produced by Nitta Gelatin Co., Ltd., beMatrix (registered trademark), gelatin HG).

[0226] [Water-soluble nonwoven fabric used (C)]

[0227] (Nonwoven Fabric-1)

[0228] The fiber strands with an average fiber diameter of 3 μm obtained by dry spinning using pullulan-1 as a water-soluble resin were collected on a collection conveyor to produce a fiber strand with a thickness of 370 μm and a weight per unit area of ​​32 g / m 2 It should be noted that the thickness refers to: according to JIS L1912:1997, 10 pieces of 3600mm in size are taken from the sample. 2 The test piece was measured using a constant pressure thickness gauge (manufactured by Ozaki Seisakusho Co., Ltd., trade name: PEACOCK (registered trademark) digital gauge, model: PDN-21, measuring pressure: 0.5±0.1 kPa, pressure foot area: 2500 mm 2 , micrometer stand model: SIS-6) measure 10 points and average the values ​​obtained.

[0229] The weight per unit area was measured in accordance with JIS L 10968.3.2 (1999). Specifically, two 200 mm square test pieces were taken, and the mass per unit area (g) under the standard state was measured. The following formula was used to calculate the weight per 1 m 2 Mass (g / m 2 ), calculate the average and round to the first decimal place.

[0230] Sm=W / A

[0231] Here, Sm: mass per unit area under standard conditions (g / m 2 )

[0232] W: The mass of the test piece under standard conditions (g)

[0233] A: Area of ​​the test piece (m 2 )

[0234] In addition, the average fiber diameter is measured by the following operation. A rectangular test piece of 14.7 cm in length and 12.7 cm in width is placed on a table without overlapping, and is left to stand for more than 48 hours under standard conditions. Thereafter, the surface of the test piece is coated with gold using "AUTO FINECOATER JEC-3000FC" (JEOL Ltd.) under the conditions of sputtering time: 120 seconds and current value: 30 mA. Next, using the ultra-deep multi-angle microscope VHX-D500 (manufactured by KEYENCE), a 3000-fold surface image is taken for a rectangular test piece of 14.7 cm × 12.7 cm, with the center set as the origin and 9 points in a grid shape parallel to the short axis direction or the long axis direction at intervals of 5 cm. For the images of each location obtained, the software included with the VHX-D500 is used to measure 200 fibers at each location that can be measured using the function between two points on a plane and average them. In addition, when the total number of points at one viewing angle was less than 200, other nearby viewing angles that did not overlap were selected and measured so that the total number of points was 200.

[0235] (Nonwoven Fabric-2)

[0236] Change the thickness to 1100μm and the weight per unit area to 95g / m 2 , except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0237] (Nonwoven Fabric-3)

[0238] Change the thickness to 280μm and the weight per unit area to 24g / m 2 , except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0239] (Nonwoven Fabric-4)

[0240] Change the thickness to 1200μm and the weight per unit area to 110g / m 2 , except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0241] (Nonwoven Fabric-5)

[0242] Change the thickness to 200μm and the weight per unit area to 18g / m 2 , except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0243] (Nonwoven Fabric-6)

[0244] Change the thickness to 620μm and the weight per unit area to 50g / m 2, except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0245] (Nonwoven Fabric-7)

[0246] Change the thickness to 140μm and the weight per unit area to 12g / m 2 , except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0247] (Nonwoven Fabric-8)

[0248] Change the thickness to 1700μm and the weight per unit area to 150g / m 2 , except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0249] (Nonwoven Fabric-9)

[0250] Change the thickness to 1300μm and the weight per unit area to 110g / m 2 , except for the above, the same operation as nonwoven fabric-1 was performed to produce a nonwoven fabric.

[0251] (Nonwoven fabric-10)

[0252] As the material of the nonwoven fabric, the water-soluble resin was changed to PVA-1, and the manufacturing method was carried out in the same manner as the nonwoven fabric-1. Thus, a nonwoven fabric having a thickness of 370 μm and a weight per unit area of ​​32 g / m was produced. 2 of nonwoven fabrics.

[0253] (Nonwoven Fabric-11)

[0254] As the material of the nonwoven fabric, the water-soluble resin was changed to PVA-2, and the manufacturing method was carried out in the same manner as the nonwoven fabric-1. Thus, a nonwoven fabric having a thickness of 370 μm and a weight per unit area of ​​32 g / m was produced. 2 of nonwoven fabrics.

[0255] (Nonwoven Fabric-12)

[0256] As the material of the nonwoven fabric, the water-soluble resin was changed to gelatin-1, and the manufacturing method was carried out in the same manner as the nonwoven fabric-1. Thus, a nonwoven fabric having a thickness of 1300 μm and a weight per unit area of ​​110 g / m was prepared. 2 of nonwoven fabrics.

[0257] (Nonwoven Fabric-13)

[0258] As the material of the nonwoven fabric, the water-soluble resin was changed to gelatin-1, and the manufacturing method was carried out in the same manner as the nonwoven fabric-1. Thus, a nonwoven fabric having a thickness of 1800 μm and a weight per unit area of ​​160 g / m was prepared. 2 of nonwoven fabrics.

[0259] (Example 1)

[0260] As a water-soluble resin, pullulan-1 was used. Specifically, a heating homogenizer was used to dissolve pullulan-1 in water to prepare an emulsion. Pullulan-1 was applied to one side of a substrate film using an applicator method so that the film thickness after drying became 5 μm, and dried at 90° C. for 20 seconds in a hot air drying dryer to form a water-soluble film (B).

[0261] Next, PLA-1 was used as a polylactic acid resin to prepare an anti-blocking layer (A). Specifically, a solution obtained by dissolving PLA-1 in dichloromethane was applied to the water-soluble film (B) formed on the substrate film using a measuring rod so that the film thickness after drying was 200 nm, and the solution was dried at 80° C. for 20 seconds in a hot air drying dryer to prepare a laminated film having an anti-blocking layer (A) and a water-soluble film (B) containing a polylactic acid resin. Thereafter, the laminated film was mechanically peeled off from the substrate film.

[0262] Thereafter, a spray of 1.6 g / m 2 After pure water is evenly applied in a manner, the nonwoven fabric-1 and the water-soluble film (B) of the laminated film are laminated. Then, the other single side of the nonwoven fabric-1 is laminated in the same manner to produce a laminated body having laminated films laminated on both sides of the nonwoven fabric-1.

[0263] (Example 2)

[0264] The thickness of the anti-adhesive layer (A) was changed to 300 nm, the thickness of the water-soluble film (B) was changed to 7 μm, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was changed to 1.2 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0265] (Example 3)

[0266] The thickness of the anti-adhesive layer (A) was changed to 120 nm, the thickness of the water-soluble film (B) was changed to 10 μm, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was changed to 1.0 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0267] (Example 4)

[0268] The thickness of the anti-blocking layer (A) was changed to 150 nm, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was changed to 0.8 g / m2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0269] (Example 5)

[0270] The thickness of the anti-adhesion layer (A) was changed to 50 nm, the thickness of the water-soluble film (B) was changed to 18 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-2, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 1.4 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0271] (Example 6)

[0272] The thickness of the anti-adhesion layer (A) was changed to 150 nm, the thickness of the water-soluble film (B) was changed to 12 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-3, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 1.0 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0273] (Example 7)

[0274] The thickness of the anti-adhesive layer (A) was changed to 100 nm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-4, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 1.0 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0275] (Example 8)

[0276] The thickness of the anti-adhesion layer (A) was changed to 500 nm, the thickness of the water-soluble film (B) was changed to 2 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-2, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 1.4 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0277] (Example 9)

[0278] The thickness of the anti-adhesion layer (A) was changed to 500 nm, the thickness of the water-soluble film (B) was changed to 8 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-5, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 0.7 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0279] (Example 10)

[0280] The thickness of the anti-adhesion layer (A) was changed to 300 nm, the resin used in the water-soluble film (B) was changed to PVA-1, the thickness of the water-soluble film (B) was changed to 7 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-10, and the spraying amount of pure water when the laminated film and the water-soluble nonwoven fabric (C) were laminated was 1.2 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0281] (Example 11)

[0282] The thickness of the anti-adhesion layer (A) was changed to 120 nm, the resin used in the water-soluble film (B) was changed to PVA-1, the thickness of the water-soluble film (B) was changed to 10 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-10, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 1.0 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0283] (Example 12)

[0284] A laminate was prepared in the same manner as in Example 1 except that the resin used in the water-soluble film (B) was changed to PVA-2 and the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-11.

[0285] (Example 13)

[0286] The thickness of the anti-adhesion layer (A) was changed to 400 nm, the resin used in the water-soluble film (B) was changed to gelatin-1, the thickness of the water-soluble film (B) was changed to 18 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-12, and the spray amount of pure water when the laminated film and the water-soluble nonwoven fabric (C) were laminated was 1.4 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0287] (Example 14)

[0288] The thickness of the anti-adhesion layer (A) was changed to 180 nm, the resin used in the water-soluble film (B) was changed to gelatin-1, the thickness of the water-soluble film (B) was changed to 16 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-13, and the spraying amount of pure water when the laminated film and the water-soluble nonwoven fabric (C) were laminated was 1.4 g / m 2A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0289] (Comparative Example 1)

[0290] The thickness of the anti-blocking layer (A) was changed to 150 nm, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was changed to 2.4 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0291] (Comparative Example 2)

[0292] The thickness of the anti-blocking layer (A) was changed to 150 nm, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was changed to 2.0 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0293] (Comparative Example 3)

[0294] The thickness of the anti-adhesive layer (A) was changed to 150 nm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-6, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 0.7 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0295] (Comparative Example 4)

[0296] A laminate was prepared in the same manner as in Example 1 except that the thickness of the anti-adhesion layer (A) was changed to 150 nm, the thickness of the water-soluble film (B) was changed to 23 μm, and the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-2.

[0297] (Comparative Example 5)

[0298] The thickness of the anti-adhesive layer (A) was changed to 150 nm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-7, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 2.0 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0299] (Comparative Example 6)

[0300] The thickness of the anti-adhesive layer (A) was changed to 150 nm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-2, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 1.0 g / m 2The water-soluble nonwoven fabric (C) was coated in such a manner that only one side was bonded to the laminated film and on the other side, pure water was sprayed at a rate of 1.0 g / m 2 A laminate was produced in the same manner as in Example 1 except that only the water-soluble film (B) was laminated and the layer structure was A / B / C / B.

[0301] (Comparative Example 7)

[0302] The thickness of the anti-adhesive layer (A) was changed to 9 nm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-8, and the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 1.8 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0303] (Comparative Example 8)

[0304] The thickness of the anti-adhesion layer (A) was changed to 1500 nm, the thickness of the water-soluble film (B) was changed to 1.5 μm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-9, and the spraying amount of pure water when the laminated film and the water-soluble nonwoven fabric (C) were laminated was 1.8 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0305] (Comparative Example 9)

[0306] The thickness of the anti-adhesion layer (A) was changed to 150 nm, the water-soluble nonwoven fabric (C) was changed to nonwoven fabric-10, and the resin used in the water-soluble film (B) was changed to PVA-1, so that the spraying amount of pure water when laminating the laminated film and the water-soluble nonwoven fabric (C) was 2.4 g / m 2 A laminate was produced in the same manner as in Example 1 except that the coating was performed in the manner of .

[0307] Table 1 shows the characteristic results of Examples 1 to 14, and Table 2 shows the characteristic results of Comparative Examples 1 to 9.

[0308] [Table 1]

[0309]

[0310] [Table 2]

[0311]

[0312] As shown in Table 1, Examples 1 to 14 were evaluated as favorable in terms of durability, water resistance, and adhesion. On the other hand, as shown in Table 2, Comparative Examples 1 to 9 were inferior in any of the items.

[0313] Specifically, regarding durability, in the comparative example, r1 and r2, which represent the structural characteristics of the laminate, did not satisfy the scope of the invention, and the laminate could not absorb the mechanical load generated during bending and was damaged, so it was judged as B.

[0314] In Comparative Example 3, the adhesion between the water-soluble film (B) and the water-soluble nonwoven fabric (C) was insufficient, and peeling easily occurred, so that the durability test and laminate cross-section observation could not be stably performed.

[0315] In Comparative Example 8, regarding adhesion, since the thickness of the anti-adhesion layer (A) was too thick at 1,500 nm, the adhesion was insufficient and the film was easily displaced from the adherend, so the film was rated as B.

[0316] Regarding water resistance, in Comparative Example 6, the water-soluble film (B) was not covered with the anti-adhesion layer (A), and in Comparative Example 7, the thickness of the anti-adhesion layer (A) was insufficient, so it was instantly dissolved by contact with water drops, and was judged as B.

[0317] Industrial Applicability

[0318] The laminate of the present invention can be particularly suitably used in medical products such as wound covering materials and anti-adhesion materials, skin care products, and skin external materials such as band-aids.

Claims

1. A laminate comprising: An anti-adhesion layer (A) comprising a polylactic acid resin and having a thickness of 10 to 500 nm; A water-soluble film (B) comprising a water-soluble resin and having a thickness of 1 to 18 μm; A water-soluble nonwoven fabric (C) containing a water-soluble resin and having a thickness of 80 to 550 μm, The anti-adhesion layer (A), the water-soluble film (B) and the water-soluble nonwoven fabric (C) are stacked in the order of (A) / (B) / (C) / (B) / (A), The image (Y) is subjected to fast Fourier transformation, and the obtained power spectrum intensity is converted into decibels. The center is set as the origin, the positive x-axis is set as zero degrees, and the semi-clockwise direction is set as a positive angle. The scatter plot obtained by integrating every 5 degrees from 0 degrees to 180 degrees satisfies the following formula 1 when the vertical axis is set as the average intensity (I) and the horizontal axis is set as the angle. The image (Y) is obtained by binarizing the image (X) according to the threshold value at which the separation degree reaches the maximum through the discriminant analysis method, and the image (X) is obtained by cutting out a digital image obtained by observing the cross section at a magnification of 500 times using a scanning electron microscope with 720×720 pixels. 0.90≤I 10-45 ÷I max ≤0.99…Formula 1 In formula 1, I 10-45 is the average intensity at angles of 10 to 45 degrees, I max Indicates the maximum average intensity from 0 to 180 degrees.

2. The laminate according to claim 1, wherein The image (Y) satisfies the following formula 2, wherein the image (Y) is obtained by binarizing the image (X) by a discriminant analysis method according to a threshold value at which the separation degree is maximized, and the image (X) is obtained by cutting out a digital image obtained by observing a cross section at a magnification of 500 times using a scanning electron microscope with 720×720 pixels, 0.30≤a÷{a+b}≤0.45…Formula 2 In Formula 2, a is the photographing area of ​​the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble non-woven fabric (C), and b represents the photographing area of ​​the gap portion surrounded by the anti-adhesion layer (A), the water-soluble film (B) and the water-soluble non-woven fabric (C).

3. The laminate according to claim 1 or 2, wherein: The water-soluble resin is pullulan.

Citation Information

Patent Citations

  • Hydraulic controller for automatic transmission

    JP1986019863B2

  • Laminate film using polylactic acid-based resin

    CA2902804A1

  • Multi-layered antiadhesion barrier

    CN101257935A

  • Laminated sheet and medical material constituted of the sheet

    JP2006289728A

  • Nonwoven fabric excellent in flexibility and water retention ability, and method for producing the same

    JP2014004705A